PENGEMBANGAN MEDIA AWETAN PORIFERA UNTUK PEMBELAJARAN BIOLOGI KELAS X - M.SHOBIRIN BM, (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Majority of students get difficulty in learning and identifying animals characteristics, for the example sponges. One of possible reason is Â the students never seen these animals by theirselvesf. Based on this problem objective of this research were to develop preserved media of sponges and describe it feasibility theoretically and empirically to support students in learning and identifying sponges. This was development research, which developed preserved media of sponge that developed by ASSURE method. The results of this research indicated that preserved media of sponges was theoretically feasible for the learning process with the percentageâ€™s 95.55% (category: very feasible) and empirically 98.5% (category: very feasible). Key words: preserved media, porifera, sponges , First Grade of Senior High School